(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2020)
Zinc Oxide (ZnO) and Aluminium doped Zinc Oxide (AZO) thin films are deposited on the glass slides by sol-gel spin coating technique. Zinc acetate dehydrate, 2 methoxyethanol, and diethanolamine are respectively used as a precursor, solvent, and stabilizer. Aluminium nitrate nonahydrate was used as the dopant source to obtain the atomic percentage of the dopant of 2%, 4%, 6% and 8%. The structural, optical, and electrical properties of the films were investigated using X-ray Diffraction (XRD), UV-visible spectrophotometry, and a Four-point probe technique respectively. The results from structural analyses show that the films are polycrystalline with a hexagonal wurtzite structure and a preferential orientation alongside the \(c\)-axis. The value obtained for the unit cell \(a=3.020\) A and \(c= 5.108\) A are in line with the reported literature. The transmittance of the films was observed within the visible region of the spectrum and the optical bandgap of the un-doped ZnO was established to be around 4.11 eV. However, the optical bandgap of the AZO films (4 and 6 at %) marginally decreases with doping concentration, which may be ascribed to the shrinkage of band effect due to the increase in carrier concentration. The lowest resistivity of \(3.53× 10^-3 Ω\) cm was observed for the doping concentration of 2% of Al. From the results, it was established that as the doping concentration increases, the thicknesses of the thin films were increased. Likewise, the increase in doping leads to a better uniformly distributed absorption spectra of the deposited AZO thin films.